INOVASI SISTEM FULL DAY SCHOOL DI MADRASAH IBTIDAIYAH DAERAH PEDESAAN - Aldi Aldi; Barsihanor Barsihanor; Muhammad Iqbal Ansari (Al-Mudarris: Journal Of Education, 2025)
This study aims to explain the implementation of Full Day School at MIN 4 Tapin and identify the supporting and inhibiting factors. This study uses a qualitative case study approach. Data collection was carried out using observation, interviews, and document studies. Data analysis was conducted through data reduction, data presentation, and conclusion drawing and verification. Data validity was ensured through triangulation of techniques and sources. The results of the study show that the Full Day School Planning Process at MIN 4 Tapin has been approved by 11 out of 12 teachers and 75% of parents. In its implementation, extracurricular and cocurricular activities have been carried out in accordance with the applicable curriculum. However, extracurricular activities have not been implemented, which has resulted in inconsistencies in the learning hours applied. This has become a subject of evaluation for the school for the coming academic year. Factors supporting the implementation of Full Day School at MIN 4 Tapin are adequate facilities and infrastructure, the condition of the teachers and parents, and a supportive social environment. The inhibiting factor is the occurrence of culture shock among students.